EVALUASI STRATEGI PENETAPAN HARGA JUAL DALAM BISNIS GOURMET LAND CAFE - Lilian Yulia Abadi (Jurnal Performa : Jurnal Manajemen dan Start-up Bisnis, 2016)
The purpose of this research is to determine the selling price in Gourmet Land cafe. This research employs cost-based pricing, value-based pricing, mark-up pricing, and competition-based pricing. This research is a descriptive qualitative research which uses the company's financial data to obtain information. Observation, interview, and documentation are used as data collection methods, while Source Triangulation is used as data analysis tool. Based on the predetermined set of criteria, eight study informants are selected. They are the owner of Head On cafe, the owner of Ronk cafe, two consumers of Gourmet Land cafe, two consumers of Head On cafe, and two consumers of Ronk cafe. Based on the data analysis results which involve production cost calculation and price comparison with each business competitor, this research concludes that Gourmet land cafe changing the first strategy and competition-based pricing is the most suitable pricing method for Gourmet Land cafe. This method is divided into three categories, namely bearish, normal, and bullish price.